OnabotulinumtoxinA in chronic migraine: predictors of response. A prospective multicentre descriptive study. (18th December 2017) - Domínguez, C.; Pozo‐Rosich, P.; Torres‐Ferrús, M.; Hernández‐Beltrán, N.; Jurado‐Cobo, C.; González‐Oria, C.; Santos, S.; Monzón, M. J.; Latorre, G.; Álvaro, L. C.; Gago, A.; Gallego, M.; et al.
Abstract : Background and purpose: OnabotulinumtoxinA is a treatment specifically approved for the prophylaxis of chronic migraine in adults. The aim of this study was to assess the effectiveness of OnabotulinumtoxinA in chronic migraine after 1 year of treatment in a real‐life setting and to identify clinical predictors of outcome. Methods: We designed a prospective multicentre study performed in 13 hospitals in Spain. Patients underwent a complete medical history and examination. They were treated with OnabotulinumtoxinA every 12 weeks for 1 year. Data about outcome, adverse events, abortive medication use, emergency room use and disability were collected at 3 and 12 months. Results: A total of 725 subjects completed the study. At 12 months, 79.3% showed >50% reduction in number of headaches per month and 94.9% reported no adverse events. Unilaterality of pain, fewer days of disability per month and milder headache at baseline were correlated with good outcome. Duration of disease <12 months increased the chances of response to treatment with OnabotulinumtoxinA (odds ratio, 1.470; 95% confidence interval, 1.123–2.174; P = 0.045). Conclusions: This study confirmed the effectiveness of treatment with OnabotulinumtoxinA after 1 year of treatment. The chances of a good outcome may be increased by starting treatment in the first 12 months after chronic migraine diagnosis.